PENGARUH ASIMETRI INFORMASI, KESESUAIAN KOMPENSASI, MORALITAS PIMPINAN DAN EFEKTIVITAS PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI EMPIRIS PADA PEGAWAI BADAN KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI UTARA) - Edward Edminister Marentek; Ventje Ilat; Jantje Tinangon (Universitas Sam Ratulangi, 2022)
Financial statements are the end of the accounting process which aims to provide information to parties related to the financial position of the company or agency which then aims to make decisions. The preparation of financial statements is independent of fraud in the preparation process. This study aims to examine the factors that influence the tendency of accounting fraud. The variables used in this study are information asymmetry, compensation suitability, leadership morality, and the effectiveness of internal controls as independent variables and vulnerability to accounti`ng variables as the dependent variable. The sample of this research is employees who work in the Regional Finance and Assets Agency of North Sulawesi Province. This study uses a judgment sampling technique sampling method. The data used in this study is primary data. Data obtained by distributing questionnaires directly to the respondents as many as 55 questionnaires. Data analysis using IBM SPSS 25. The results show that information asymmetry has a positive effect on the tendency of accounting fraud, compensation suitability has no effect on the incidence of accounting fraud, leadership morality has no effect on the incidence of accounting fraud, and the effectiveness of internal controls has no effect on the tendency of accounting fraud.